Critical applied stresses for a crack initiation from a sharp V-notch (Fracture and Structural Integrity, 2014)
The aim of the paper is to estimate a value of the critical applied stress for a crack initiation from a sharp V-notch tip. The classical approach of the linear elastic fracture mechanics (LELM) was generalized, because the stress singularity exponent differs from 0.5 in the studied case. The value of the stress singularity exponent depends on the V-notch opening angle. The finite element method was used for a determination of stress distribution in the vicinity of the sharp V-notch tip and for the estimation of the generalized stress intensity factor depending on the V-notch opening angle. Critical value of the generalized stress intensity factor was obtained using stability criteria based on the opening stress component averaged over a critical distance d from the V-notch tip and generalized strain energy density factor. Calculated values of the critical applied stresses were compared with experimental data from the literature and applicability of the LEFM concept is discussed.
Keywords: V-notch